Elasmobranch Responses to Experimental Warming, Acidification, and Oxygen Loss—A Meta-Analysis - Santos, Catarina Pereira; Sampaio, Eduardo; Pereira, Beatriz P.; Pegado, Maria Rita; Borges, Francisco O.; Wheeler, Carolyn R.; Bouyoucos, Ian A.; Rummer, Jodie L.; Frazão Santos, Catarina; Rosa, Rui (Frontiers in Marine Science, 2021)
Despite the long evolutionary history of this group, the challenges brought by the Anthropocene have been inflicting an extensive pressure over sharks and their relatives. Overexploitation has been driving a worldwide decline in elasmobranch populations, and rapid environmental change, triggered by anthropogenic activities, may further test this group's resilience. In this context, we searched the literature for peer-reviewed studies featuring a sustained (>24 h) and controlled exposure of elasmobranch species to warming, acidification, and/or deoxygenation: three of the most pressing symptoms of change in the ocean. In a standardized comparative framework, we conducted an array of mixed-model meta-analyses (based on 368 control-treatment contrasts from 53 studies) to evaluate the effects of these factors and their combination as experimental treatments. We further compared these effects across different attributes (lineages, climates, lifestyles, reproductive modes, and life stages) and assessed the direction of impact over a comprehensive set of biological responses (survival, development, growth, aerobic metabolism, anaerobic metabolism, oxygen transport, feeding, behavior, acid-base status, thermal tolerance, hypoxia tolerance, and cell stress). Based on the present findings, warming appears as the most influential factor, with clear directional effects, namely decreasing development time and increasing aerobic metabolism, feeding, and thermal tolerance. While warming influence was pervasive across attributes, acidification effects appear to be more context-specific, with no perceivable directional trends across biological responses apart from the necessary to achieve acid-base balance. Meanwhile, despite its potential for steep impacts, deoxygenation has been the most neglected factor, with data paucity ultimately precluding sound conclusions. Likewise, the implementation of multi-factor treatments has been mostly restricted to the combination of warming and acidification, with effects approximately matching those of warming. Despite considerable progress over recent years, research regarding the impact of these drivers on elasmobranchs lags behind other taxa, with more research required to disentangle many of the observed effects. Given the current levels of extinction risk and the quick pace of global change, it is further crucial that we integrate the knowledge accumulated through different scientific approaches into a holistic perspective to better understand how this group may fare in a changing ocean.